2021
DOI: 10.1016/j.immuni.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal profiling of respiratory and systemic immune responses reveals myeloid cell-driven lung inflammation in severe COVID-19

Abstract: Immune response dynamics in coronavirus disease 2019 and their severe manifestations have largely been studied in circulation. Here, we examined the relationship between immune processes in the respiratory tract and circulation through longitudinal phenotypic, transcriptomic, and cytokine profiling of paired airway and blood samples from patients with severe COVID-19 relative to heathy controls. In COVID-19 airways, T cells exhibited activated, tissue-resident, and protective profiles; higher T cell frequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
337
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(380 citation statements)
references
References 90 publications
19
337
4
1
Order By: Relevance
“…Similar phenomenon have been noted in human subjects, with one study describing an association between SARS-CoV-2 viral burden, IL-6 levels, and increased risk of death 24 . Similar to studies of post-mortem lung tissue or BALs from patients suffering from COVID-19, we observed a significant increase in the numbers of S100a8+ granulocytes in the lung parenchyma 4,[6][7][8] . S100a8/9 and TLR4 signaling mediate the emergence of a dysregulated neutrophil population that promotes SARS-CoV-2 disease 18 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar phenomenon have been noted in human subjects, with one study describing an association between SARS-CoV-2 viral burden, IL-6 levels, and increased risk of death 24 . Similar to studies of post-mortem lung tissue or BALs from patients suffering from COVID-19, we observed a significant increase in the numbers of S100a8+ granulocytes in the lung parenchyma 4,[6][7][8] . S100a8/9 and TLR4 signaling mediate the emergence of a dysregulated neutrophil population that promotes SARS-CoV-2 disease 18 .…”
Section: Discussionsupporting
confidence: 87%
“…Innate immunity to SARS-CoV-2 begins with a limited interferon (IFN) response and production of inflammatory cytokines (IL-6, Il-1β, TNFα, IL-8) by respiratory epithelial cells or alveolar macrophages [3][4][5][6]7 . As shown in bronchoalveolar lavages (BAL) of COVID-19 patients, this innate immune response coincides with robust infiltration of neutrophils, monocytes, and dendritic cells into the lung airways 6,8 . Monocytes in the lung parenchyma can be divided into subpopulations characterized by their expression of Ly6C; Ly6C high classical monocytes are pro-inflammatory, whereas Ly6C low non-classical monocytes promote wound healing 9,10 .…”
mentioning
confidence: 85%
“…Pathogenic changes in the monocytic compartment regarding phenotypes and function and an increase in immature neutrophils are central hallmarks of COVID-19 [424]. Macrophage activity drives both inflammation and much of the pathology in COVID-19 patients [425,426]. These cells act as sentinels to limit early viral replication by initiating an IFN-I response and an inflammatory response to recruit additional immune cells [427].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…While most COVID-19 patients have mild symptoms, about 15% of patients develop severe COVID-19 often with fatal outcomes, and scientists have been on the hunt to understand the underlying immune mechanisms driving disease severity. In a recent study in Immunity, Szabo et al 1 provide comprehensive longitudinal insights into the phenotypical and functional shifts of T cells, monocytes and macrophages driving inflammation in the lungs of patients with severe COVID-19.…”
mentioning
confidence: 99%